Intra-articular yttrium 90 in rabbits. Comparison of behaviour of various radiocolloids in rabbits and in man. - Gumpel, J M (1978)
Comparative studies of the retention of various yttrium 90 radiocolloids and of noncolloidal yttrium 90 chloride were performed in rabbits with arthritis induced in one knee. Two colloids, the citrate and resin forms, showed a statistically significant difference in retention between inflamed and normal knees, isotope being retained better in the normal knee. Marked differences were found in the handling of the various yttrium preparations in rabbits compared with previously reported results in man. These differences suggest that the rabbit with induced arthritis is not a suitable model in which to test retention of different radiocolloids before use in man.